2018
DOI: 10.1002/jcc.25767
|View full text |Cite
|
Sign up to set email alerts
|

Analytic atomic gradients in the fermi‐löwdin orbital self‐interaction correction

Abstract: We derived, implemented, and thoroughly tested the complete analytic expression for atomic forces, consisting of the Hellmann‐Feynman term and the Pulay correction, for the Fermi‐Löwdin orbital self‐interaction correction (FLO‐SIC) method. Analytic forces are shown to be numerically accurate through an extensive comparison to forces obtained from finite differences. Using the analytic forces, equilibrium structures for a small set of molecules were obtained. This work opens the possibility of routine self‐inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…This decrease in thermochemical error when applying SIC to LDA is in good agreement with previous reports on the subject. [16,47,49,50,127,128,130,131] The fact that SCAN performs better than LDA-FLO-SIC for atomization energies has also been noted before. [49]…”
Section: Gas Phasesupporting
confidence: 70%
See 2 more Smart Citations
“…This decrease in thermochemical error when applying SIC to LDA is in good agreement with previous reports on the subject. [16,47,49,50,127,128,130,131] The fact that SCAN performs better than LDA-FLO-SIC for atomization energies has also been noted before. [49]…”
Section: Gas Phasesupporting
confidence: 70%
“…[123] Furthermore, FLO-SIC and RSIC overbind and deliver very similar Δ f ,g H M ð298.15 KÞ, with a difference of only 3 kcal mol À1 . Both the overbinding tendency of FLO-SIC [47,49,128] and RSIC [47,127] as well as the close agreement between the two SIC approaches for standard enthalpies of formation [47] have been detailed in previous studies. The MAEs of both SIC methods are smaller than the MAE of LDA by about 50 kcal mol À1 .…”
Section: Gas Phasementioning
confidence: 70%
See 1 more Smart Citation
“…More recently, Pederson et al . showed that unitarily invariant Fermi‐Löwdin orbitals proposed by Luken can be used to perform self‐consistent SIC calculations within the Fermi‐Löwdin orbital self‐interaction correction (FLO‐SIC) method.…”
Section: Introductionmentioning
confidence: 99%
“…The Fermi-Löwdin Orbital Self-Interaction Corrected DFT (FLOSIC-DFT) is viewed as a further step in developing methods for more universal treatment of unphysical SIE in DFT [43]. The main difference with respect to former SIE-corrected versions relies on how energy-minimizing orbitals are variably obtained, towards SIE-free properties, with the present variant offering computational advantages and with analytical gradients also available [44].…”
Section: Summary Of Some Emerging Dft Methodsmentioning
confidence: 99%